Answer:
9x^2
Explanation:
It is given that:
x ( x + y ) = 27
If one manipulates the equation, by dividing by x, they get:
x + y = 27/x
It is also given that:
y ( x + y ) = 54
Again, manipulate the equation, only this time, divide by y,
x + y = 54/y
It is obvious that;
x + y = x + y
Yet this was proven;
x + y = 27/x
x + y = 54/y
Therefore, the following has to be true;
27/x = 54/y
To sove the proportion, use cross products;
27/x = 54/y
54x = 27y
Inverse operations:
54x = 27y
/27 /27
y = 2x
Substitute;
(x + y)
y = 2x
= (x + 2x)
= 3x
Now solve:
(3x)^2
9x^2